PENYELESAIAN SENGKETA WARIS MELALUI MEDIASI DI PENGADILAN AGAMA DAN PENGADILAN NEGRI DI INDONESIA - Nayla Azzahra Khaerunnisa; Sidi Ahyar Wiraguna (Jurnal Riset Multidisiplin Edukasi, 2025)
Inheritance disputes in Indonesia are often prolonged due to legal pluralism involving Islamic law, customary law, and the Civil Code. In response, the Supreme Court mandates mediation in all civil cases, including inheritance disputes, under PERMA No. 1 of 2016. This study examines mediation practices in inheritance cases at Religious Courts and District Courts, and identifies factors influencing their effectiveness. Using a qualitative comparative case study approach, data were collected through in-depth interviews with judges, mediators, court clerks, and disputing parties, supplemented by case document analysis. Findings reveal that mediation at Religious Courts is normative and educative, constrained by the rigid principles of Islamic inheritance law (faraid), limiting negotiation space. In contrast, District Courts allow more flexible, problem-solving approaches under civil law. Despite differences, both courts emphasize empathy, family reconciliation, and cultural sensitivity. Success depends on mediator competence, parties’ psychological readiness, and socio-cultural context. The study concludes that differentiated mediation guidelines—tailored to the substantive legal basis of each case—are essential to transform mediation from procedural formality into a meaningful, just, and humane dispute resolution mechanism.